(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The “Everyone to Learn Program” of the Ministry of National Education, allowed for the consolidation of strategies to strengthen competencies in the use of Information and Communication Technologies (ICT). Among teachers from schools with the lowest performance according to state exams. The methodology used prioritized a qualitative approach and pedagogical action research; data collection techniques included field diaries, semi-structured interviews, and participant observation. The process was guided by three methodological phases: deconstruction, reconstruction, and evaluation. The results showed a positive change in teachers’ attitudes and motivation toward ICT, as well as increased collaboration and knowledge sharing among them. The study concluded that teacher training in ICT competencies should be increased, as this type of strategy enhances pedagogical practices and redefines the role of educators.